Perbaikan Histopatologi Pankreas Tikus Hiperglikemia setelah Pemberian Ekstrak Etanol Kulit Batang Pakoba (Syzygium luzonense (Merr.) Merr.) - Mario Walean; Rostina Melpin; Mervina Rondonuwu; Kinzie Feliciano Pinontoan (Fakultas Biologi | Universitas Jenderal Soedirman, 2020)
Pakoba as an endemic plant in North Sulawesi has ethnomedical benefits in treating diabetes. The purpose of this study was to determine the histopathological of pancreatic hyperglycemic rats induced by alloxan by the administration of pakoba stem bark ethanol extract (PSBEE). Rats with an average weight of 150-200 gr were divided into 5 treatment groups. Group I as a normal control without alloxan administration then group II alloxan control, group III were treated with glibenclamide 5 mg/kgbw, groups IV and V were treated with PSBEE 150 and 300 mg/kgbw oral gavage. Phytochemical screening results of PSBEE contain a lot of alkaloids, flavonoids, and tannins. A dose of 300 mg/kgbw PSBEE is better in repair pancreatic cells in hyperglycemia rats compared with a dose of 150 mg/kgbw. There needs further research to know the antioxidant activity, the mechanism of the active compound content of the pakoba stem bark as an antihyperglycemic.